(untitled) (Journal of the College of Basic Education, 2023)
Societies have been exposed (in recent years) to many changes, which includedvarious aspects of life, which had a direct impact on what society and its institutions expecteducation necessitates a change in the objectives, contents and methods of education, because the educational system representsThe basis on which many personal characteristics of the learners grow and the value of any systemeducation is determined by its ability to achieve its goals, as education is one of the most importantIn the lives of peoples, as it shapes man’s thought, his cultural awareness and his social role.